Factors influencing the mental health of caregivers of children with cerebral palsy - Kouther, Dania A.; Shakir, Murug O.; Alhumaidah, Reem A.; Jamaluddin, Huda A.; Jaha, Afnan Y.; Alshumrani, Mesbah J.; Hakami, Alqassem Y. (Frontiers in Pediatrics, 2022)
Objectives: Caregivers of children with cerebral palsy have a huge burden which might affect their mental health. This study aimed to determine the different factors affecting the mental health of caregivers of children with cerebral palsy and to raise awareness among healthcare providers. Methods: A cross-sectional study was conducted among caregivers of children with cerebral palsy in National Guard Health Affairs-Jeddah, Saudi Arabia, using the Depression Anxiety Stress Scale-21, which is a validated questionnaire that assesses: depression, anxiety, and stress. This questionnaire was used to assess the mental health of the caregivers. In addition, factors that reflected the child’s health condition, such as visual impairment, number of emergency department visits, and number of Pediatric Intensive Care Unit admissions were also reported to investigate the impact on the caregiver’s mental health. Results: The study sample consisted of 40 caregivers, of which 72.5% were mothers. According to the Depression Anxiety Stress Scale-21 score, 12.5% (n=5) of the caregivers had moderate depression scores, 10% (n=4) revealed extremely severe depression, and 10% (n=4) showed moderate anxiety. Furthermore, 12.5% (n=5), 15% (n=6), and 7.5% (n=3) of the caregivers have scored as moderate, severe, and extremely severe stress levels, respectively. Caregivers’ depression, anxiety, and stress scores were significantly (p ≤ 0.05) associated with the impact of vision of their dependent children, frequent hospital admissions, and frequent emergency department visits. Increased Pediatric Intensive Care Unit admissions in the past year were also significantly associated with higher caregiver anxiety scores. Conclusion: To the best of our knowledge, the dimension of caregivers’ stress and anxiety and their association with the children’s dependency level is not well documented in our region. Caregivers of children with cerebral palsy reported having mental health challenges associated with the children’s visual impairment, frequent need for acute medical care, and hospital admissions. Healthcare workers should provide early and proactive planning of medical and social support for children with cerebral palsy and their families using a family-centered approach.